Integral of (2-x)dx dx
The solution
Detail solution
-
Let u=2−x.
Then let du=−dx and substitute −du:
-
The integral of a constant times a function is the constant times the integral of the function:
∫(−u)du=−∫udu
-
The integral of un is n+1un+1 when n=−1:
∫udu=2u2
So, the result is: −2u2
Now substitute u back in:
−2(2−x)2
-
Now simplify:
−2(x−2)2
-
Add the constant of integration:
−2(x−2)2+constant
The answer is:
−2(x−2)2+constant
The answer (Indefinite)
[src]
/ 2
| (2 - x)
| (2 - x)*1 dx = C - --------
| 2
/
2x−2x2
The graph
Use the examples entering the upper and lower limits of integration.